2022
DOI: 10.1111/vcp.13197
|View full text |Cite
|
Sign up to set email alerts
|

Markers of inflammation in free‐living African elephants (Loxodonta africana): Reference intervals and diagnostic performance of acute phase reactants

Abstract: Introduction Acute phase reactants (APRs) have not been investigated in free‐living African elephants (Loxodonta africana), and there is little information about negative APRs albumin and serum iron in elephants. Objectives We aimed to generate reference intervals (RIs) for APRs for free‐living African elephants, and to determine the diagnostic performance of APRs in apparently healthy elephants and elephants with inflammatory lesions. Methods Stored serum samples from 49 apparently healthy and 16 injured free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 58 publications
(219 reference statements)
0
18
0
Order By: Relevance
“…Performance goals derived from estimates of biological variation are available for selected APRs in dogs, and total allowable error based on analytical performance and consensus between the two authors of this review has been suggested for SAA (Table 5). 34,49 Although not ideal, these could be useful when evaluating validation results for APR assays in zoo and wildlife species 34,36 …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Performance goals derived from estimates of biological variation are available for selected APRs in dogs, and total allowable error based on analytical performance and consensus between the two authors of this review has been suggested for SAA (Table 5). 34,49 Although not ideal, these could be useful when evaluating validation results for APR assays in zoo and wildlife species 34,36 …”
Section: Methodsmentioning
confidence: 99%
“…It has been recommended that 20–30 animals be included in each group, and that the presence or absence of inflammation is clear, based on clinical signs, other laboratory testing, or postmortem findings 10 . Evaluation of overlap performance is commonly performed in nondomesticated mammal APR studies, as noted in Tables 1‐4 13,14,16,22,23,32–37,39,40,42–46,50 . We recommend that to optimize this stage, clinical pathologists work closely with clinicians to gather information about the nature of the putative inflammatory disease and sample handling, such as sample type, storage conditions, number of freeze‐thaw cycles, diagnosis, chronicity of disease, a sample taken before or during treatment, availability of repeated samples from one animal.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations